2018
DOI: 10.1016/j.colegn.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and supporting nursing students on clinical placements: Doing the right thing

Abstract: Problem: Pre registration nursing students do not always feel supported by Registered Nurses during their clinical placements. To help develop and refine clinical skills, in order to deliver safe, competent nursing care, nursing students rely on Registered Nurses to teach and support them in their clinical learning. Background: Pre-registration nursing students in Australia must undertake a minimum of 800 clinical placement hours as part of their undergraduate nursing education. Registered Nurses are required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…47 Though research from other health professions shows students do not always feel supervision is provided in a supportive manner. 48 According to the Australian professional capabilities for medical radiation practitioners 49 (page 18), Australian practitioners are expected to 'use appropriate strategies to effectively supervise students in the work environment and deliver feedback (verbal and written) to the student and the education provider on their performance'. This is an important recognition of the important role qualified mentors play in the development of coping mechanisms including learning ways to stay safe, identifying and managing stress and other demands not directly related to clinical placement.…”
Section: Support From Clinical Mentors and Supervisorsmentioning
confidence: 99%
“…47 Though research from other health professions shows students do not always feel supervision is provided in a supportive manner. 48 According to the Australian professional capabilities for medical radiation practitioners 49 (page 18), Australian practitioners are expected to 'use appropriate strategies to effectively supervise students in the work environment and deliver feedback (verbal and written) to the student and the education provider on their performance'. This is an important recognition of the important role qualified mentors play in the development of coping mechanisms including learning ways to stay safe, identifying and managing stress and other demands not directly related to clinical placement.…”
Section: Support From Clinical Mentors and Supervisorsmentioning
confidence: 99%
“…Engagement in clinical placements as support for the educational development of undergraduate nurses is supported by a wealth of literature (Anderson et al . 2018; Birks et al . 2017; Patterson et al .…”
Section: Introductionmentioning
confidence: 99%
“…To assist students with successfully navigating the clinical environment, RNs are expected to guide their learning and education (Anderson et al . 2018). This is also emphasized in the Australian Nursing and Midwifery Board's standards of practice, which states ‘The RN actively fosters a culture of safety and learning that includes engaging with health professionals and others, to share knowledge and practice that supports person‐centred care’ (Nursing and Midwifery Board of Australia 2016, Standard 2.7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have focused on the broad dimensions of psychosocial factors. As a result of a study in Australia in 2018 by Anderson et al it was shown that nursing students are not supported by nursing staff because nurses are not aware of their educational responsibilities towards students (13). The results of a study in Jamaica in 2015, by Lawal et al, showed that more than half of the students believed that the clinical environments were not a friendly environment and that it was necessary to correct these environments (14).…”
Section: Introductionmentioning
confidence: 99%